SMILES: Potentially Higher Ionizing Photon Production Efficiency in Overdense Regions - Yongda Zhu; Stacey Alberts; Jianwei Lyu; Jane Morrison; George H. Rieke; Yang Sun; Jakob M. Helton; Zhiyuan Ji; Rachana Bhatawdekar; Nina Bonaventura; Andrew J. Bunker; Xiaojing Lin; et al. (The Astrophysical Journal)
The topology of reionization and the environments where galaxies efficiently produce ionizing photons are key open questions. For the first time, we investigate the trend between ionizing photon production efficiency, ξ _ion , and galaxy overdensity, $log(1+δ )$ . We analyze the ionizing properties of 79 galaxies between 1.0 < z < 5.2 using JWST NIRSpec medium-resolution spectra from the Systematic Mid-infrared Instrument Legacy Extragalactic Survey (SMILES) program. Among these, 67 galaxies have H α coverage, spanning 1.0 < z < 3.1. The galaxy overdensity, $log(1+δ )$ , is measured using the JADES photometric catalog, which covers the SMILES footprint. For the subset with H α coverage, we find that $log{ξ }_{{\rm{ion}}}$ is positively correlated with $log(1+δ )$ , with a slope of $0.9{4}_{-0.46}^{+0.46}$ . Additionally, the mean ξ _ion for galaxies in overdense regions ( $log(1+δ )\gt 0.1$ ) is 2.43 times that of galaxies in lower density regions ( $log(1+δ )\lt 0.1$ ). This strong trend is found to be independent of redshift evolution. Furthermore, our results confirm the robust correlations between ξ _ion and the rest-frame equivalent widths of the [O iii ] or H α emission lines. Our results suggest that galaxies in high-density regions are efficient producers of ionizing photons.